Peran Film Dilan 1990 dalam Membangun Imajinasi Wisata Kota Bandung Melalui Interaksi Tokoh Utama - Recta Yogi Widi Astutik; Tava Julia Putri; Muhammad Athoillah; Muhammad Shofaul Fahmi Priyono; Ariel Dimas Hidayatullah; Arsih Amalia Chandra Permata6; Wiyata Wiyata (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This research explores the role of the film Dilan 1990 in shaping the tourism imagination of Bandung through the interaction of its main characters and the representation of urban space within the narrative. Employing a descriptive qualitative approach with semiotic analysis and cultural representation theory, the research examines how visual and narrative elements in the film influence audience perceptions of Bandung as a cultural and nostalgic tourist destination. The findings reveal that Dilan 1990 successfully reconstructs collective memory of 1990s Bandung through cultural symbols, youth communication styles, and the depiction of urban spaces such as schools, streets, and city landmarks like Gedung Merdeka and Jalan Asia Afrika. The interpersonal communication between Dilan and Milea enhances the emotional depth and appeal of these urban settings, embedding them within a romantic narrative that resonates with viewers. This representation fosters an emotional connection between the audience and the locations portrayed, contributing to the emergence of film-induced tourism. The study concludes that film can serve as an effective medium for promoting cultural tourism, while also emphasizing the importance of interpersonal communication in enhancing tourism appeal through emotional and symbolic engagement.